Aseismic zone and earthquake segmentation associated with a deep subducted seamount in Sumatra - Singh, S; Hananto, N; Mukti, M; Robinson, D; Das, S; Chauhan, A; Carton, H; Gratacos, B; Midnet, S; Djajadihardja, Y; Harjono, H (2011)
The subduction of large topographic features such as seamounts has been linked to plate locking1-7, earthquake generation8 and segmentation6, as well as crustal erosion9,11 at subduction zones. However, the role of subducted features in the generation of megathrust earthquakes has been difficult to discern because traditional imaging techniques are limited to the upper 12 km of the Earth's crust12, whereas these ruptures initiate at depths of 20-40 km (ref. 13). Here we use a deeply penetrating imaging technique with a low-energy source to identify a seamount 3-4 km high and 40 km wide that has been subducted to a depth of 30-40 km below the Sumatra forearc mantle. We find that the seamount has remained intact despite more than 160 km of subduction, and that there is no seismic activity either above or below the seamount. We therefore conclude that the coupling between the seamount and overriding plate is weak and aseismic 14. We suggest that the subduction of a topographic feature such as a seamount could lead to the segmentation of the subduction zone, which could in turn reduce the maximum size of megathrust earthquakes in these localities. © 2011 Macmillan Publishers Limited. All rights reserved.